ANALISIS KEKUATAN DEMOKRASI DALAM ERA KOALISI KABINET PASCA REFORMASI 1998 DI INDONESIA (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2020)
This study is motivated by an analysis of the reality of the multi-party presidential system which is the main aspect of the way back in the governance system in Indonesia, starting from the old order until the reform era in 1998, the plurality structure of the party became a forerunner to the survival of the coalition in the formulation of the Indonesian government cabinet. Consideration that is the prospect of seizing seats in the cabinet coalition is usually focused on the opportunity structure (strategy entry), where the strategy entry refers to the calculation of three important considerations that are political calculations, namely the cost of entering the arena (cost of entry), various benefits (benefits of office), and the possibility of obtaining support from voters (probably of receiving electoral support). In the target of realizing the political goals of the coalition parties, the main approach taken is to develop mutual benefits, namely the benefits of enjoying power. So that in formulating indicators of the success of a democratic country, this study also presents a comparison related to the implementation of a presidential government system in the United States and a parliamentary government system in the United Kingdom that has resulted in a democratic and stable government, as well as realizing a multi-party presidential system as a whole and optimizing dual functions businessman in internal political parties.